Hello, universe - Kelly, Erin Entrada 1977- (Greenwillow Books, an imprint of HarperCollins Publishers, 2017)
Lives of four misfits are intertwined when a bully's prank lands shy Virgil at the bottom of a well and Valencia, Kaori, and Gen band together in an epic quest to find and rescue him
Cover: Also available as an ebook
Keywords: JUVENILE FICTION / Social Issues / Friendship / bisacsh; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance / bisacsh; JUVENILE FICTION / Social Issues / Special Needs / bisacsh; Friendship; Missing children; Bullying; Hearing impaired; Psychic ability; Sisters; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance; JUVENILE FICTION / Social Issues / Special Needs; Jugendbuch